Predicting environmental biodegradability using initial rates: mineralization of cellulose, guar and their semisynthetic derivatives in wastewater and soil - Hart-Cooper, William M.; Kalla, Nabeel; Klamczynski, Artur; Torres, Lennard; Glenn, Gregory M.; Cunniffe, Julia; Johnson, Kaj; Orts, William J. (Frontiers in Materials, 2024)
Microplastic pollution is a growing concern, and natural materials are being increasingly sought as plastic alternatives. Semisynthetic biopolymers occupy a grey area between natural and synthetic materials and are often presented as green alternatives to conventional plastic. They can be water-soluble or insoluble, and are ubiquitous in commercial products as thickeners, films, filters, viscosity modifiers and coatings. This work compares the mineralization kinetics of cellulose, guar and several of their commercialized derivatives using a simple pseudo first-order kinetic model to extrapolate half-lives and lifetimes, while identifying the levers that influence the mineralization rates of these ubiquitous materials. Industrial composting rates were consistently faster than those of wastewater. While partially substituted biopolymers exhibited measurable degradation, kinetic analysis revealed this effect could be entirely accounted for by the fraction of unsubstituted biopolymer. Surprisingly, the initial rates of highly substituted biopolymers exhibited persistence on par with conventional plastics over the experimental durations studied.